(untitled) (Research, Society and Development, 2020)
The objective of the present work was to determine the antioxidant potential of the essential oil of the leaves of Campomanesia xanthocarpa. The technique used for the extraction of the essential oil was hydrodistillation using the Clevenger apparatus and the identification of the chemical composition of the essential oil by gas chromatography coupled to the mass spectrometry (GC-MS). The antioxidant potential was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH•), ferric ion reducing antioxidant power (FRAP), and β-carotene/linoleic acid co-oxidation. By GC-MS analysis, 47 compounds were identified, and the major class was the hydrocarbon sesquiterpenes (46.80%) with the major compounds: bicyclogermacrene (8.29%); globulol (5.67%); τ-murolol (5.59%); β-karyophylene (5.28%); germacrene D (5.03%); δ-cadinene (4.76%); τ-cadinol (4.51%) and linalool (4.17%). The results found for the antioxidant activity by β-carotene/linoleic acid co-oxidation system indicated that the essential oil of C. xanthocarpa showed a high antioxidant potential at 1.00 mg/mL and an intermediate potential at the other concentrations tested. The antioxidant activity of the essential oil by the FRAP method was 3.83 ± 1.99 µMol Fe+2/mg. Therefore, the oil essential from C. xanthocarpa leaves showed antioxidant potential by β-carotene/linoleic acid co-oxidation system, and FRAP, encouraging the inclusion of this species in the list of natural antioxidants for application in the food, cosmetic and pharmaceutical fields.